2022
DOI: 10.3389/fmed.2022.1065625
|View full text |Cite
|
Sign up to set email alerts
|

Positive SARS-CoV-2 detection on intraoperative nasopharyngeal viral testing is not associated with worse outcomes for asymptomatic elective surgical patients

Abstract: BackgroundIt has been demonstrated that surgical patients with COVID-19 are at increased risk for postoperative complications. However, this association has not been tested in asymptomatic elective surgical patients.MethodsA retrospective cohort study among elective gynecological and spine surgery patients at a single tertiary medical center from July 2020 through April 2022 (n = 1,130) was performed. The primary endpoint was prolonged (>75th percentile for the corresponding surgical service) length of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Recently, Quinn et al found no significant correlation between postoperative outcomes of COVID-19 patients and infection within 4 weeks or 7 weeks before surgery, as well as vaccination status [16]. Another study on elective spine and gynecologic surgeries suggested that asymptomatic COVID-19 patients with incidental intraoperative SARS-CoV-2 positivity did not experience worse outcomes [17]. An updated guideline from the United Kingdom recommended that patients should avoid elective surgery within 2 weeks after SARS-CoV-2 infection [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Quinn et al found no significant correlation between postoperative outcomes of COVID-19 patients and infection within 4 weeks or 7 weeks before surgery, as well as vaccination status [16]. Another study on elective spine and gynecologic surgeries suggested that asymptomatic COVID-19 patients with incidental intraoperative SARS-CoV-2 positivity did not experience worse outcomes [17]. An updated guideline from the United Kingdom recommended that patients should avoid elective surgery within 2 weeks after SARS-CoV-2 infection [18].…”
Section: Discussionmentioning
confidence: 99%